N-cyclohexyl-2-[5-(4-pyridyl)-4-(p-tolyl)-4H-1,2,4-triazol-3-ylsulfanyl]-acetamide dihydrate: Synthesis, experimental, theoretical characterization and biological activities - Orek, Cahit; Koparir, Pelin; Koparir, Metin (Pergamon-Elsevier Science Ltd, 2012)
The triazol compound N-cyclohexyl-2[5-(4-pyridyl)-4-(p-tolyl)-4H-1,2,4-triazol-3-ylsulfanyl]-acetamide dihydrate has been synthesized and characterized by H-1 NMR, C-13 NMR, IR, and X-ray single-crystal determination. The molecular geometry, vibrational frequencies and gauge including atomic orbital (CIAO) 1H and 13C NMR chemical shift values of III in the ground state have been calculated using the density functional method (B3LYP) with the 6-31G(d) basis set. The calculated results show that the optimized geometry can well reproduce the crystal structure, and the theoretical vibrational frequencies and chemical shift values show good agreement with experimental values. The energetic behavior of III in solvent media was examined using the B3LYP method with the 6-31G(d) basis set by applying the Onsager and the polarizable continuum model (PCM). The predicted nonlinear optical properties of III are greater than ones of urea. In addition. OFT calculations of molecular electrostatic potentials, frontier molecular orbitals and thermodynamic properties of III were carried out at the B3LYP/6-31G(d) level of theory. The title compound was screened for antibacterial, antifungal and antioxidant activities. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: N-cyclohexyl-2-[5-(4-pyridyl)-4-(p-tolyl)-4H-12,4-triazol-3-ylsulfanyl]-acetamide dihydrate; DFT; NMR; IR spectra; Biological effects